An improved data-collection form for the surveillance of HIV infection in Italy (Italian Journal of Public Health, 2010)
Background: The data-collection form used for Italy's recently established national HIV surveillance systemdoes not include sufficient information to thoroughly describe the dynamics of the epidemic. In addition,comparisons with data from other European countries are difficult. To address this issue, we have developeda more detailed form based on forms used in other European countries.Methods: Data-collection forms used in other countries were evaluated, and the information collected wascategorised by topic. Based on this evaluation, a form was developed for use in Italy.Results: The forms used in other countries are more detailed than the Italian form, and we propose addingthe following information to the Italian form: i) the year of entry in Italy for non-nationals; ii) testing pattern(i.e., the number of tests in the previous two years and during lifetime); iii) whether or not infection wasrecent, based on the antibody avidity index, and which test and cut-off were used; iv) whether or not testingwas performed in the acute phase of infection, based on symptoms; and v) a checklist of reasons forundergoing testing. We also added a “Comments” section for information not recorded elsewhere on theform.Discussion: The more detailed form will allow for a more thorough description of the characteristics of newlyinfected persons and of the dynamics of the epidemic in Italy, which is fundamental for prevention and controlinitiatives. It will also allow for comparisons to be made against data from other European countries, revealingimportant similarities and differences.
Keywords: HIV; AIDS; surveillance